2010
DOI: 10.1007/s10096-010-1004-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 16S rRNA methylases among different species of Gram-negative bacilli with high-level resistance to aminoglycosides

Abstract: 16S rRNA methylases confer high-level resistance to most aminoglycosides in Gram-negative bacteria. Seven 16S rRNA methylase genes, armA, rmtA, rmtB, rmtC, rmtD, rmtE and npmA, have been identified since 2003. We studied the distribution of methylase genes in more than 200 aminoglycoside-resistant Gram-negative clinical isolates collected in 2007 at our hospital in Shanghai, China. 16S rRNA methylase genes were amplified by polymerase chain reaction (PCR) among 217 consecutive clinical isolates of Gram-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 30 publications
5
46
0
Order By: Relevance
“…Additional antimicrobial susceptibility testing by broth microdilution (9,10) revealed that all 39 fosA3-positive isolates were also resistant to florfenicol, cefotaxime, gentamicin, and tetracycline but susceptible to colistin (see Table S1). PCR amplification and sequencing (11,12) revealed that all of the fosA3-positive isolates also harbored bla CTX-M genes, and 15 (38.5%) of them produced CTX-M-55 (Table 1). In addition, 29 (74.4%), 22 (56.4%), 20 (51.3%), and 20 (51.3%) isolates carried floR, tet(A), bla TEM-1 , and rmtB genes, respectively (Table 1).…”
mentioning
confidence: 99%
“…Additional antimicrobial susceptibility testing by broth microdilution (9,10) revealed that all 39 fosA3-positive isolates were also resistant to florfenicol, cefotaxime, gentamicin, and tetracycline but susceptible to colistin (see Table S1). PCR amplification and sequencing (11,12) revealed that all of the fosA3-positive isolates also harbored bla CTX-M genes, and 15 (38.5%) of them produced CTX-M-55 (Table 1). In addition, 29 (74.4%), 22 (56.4%), 20 (51.3%), and 20 (51.3%) isolates carried floR, tet(A), bla TEM-1 , and rmtB genes, respectively (Table 1).…”
mentioning
confidence: 99%
“…Indeed, combined production of nucleotidyl-, phosphoryl-, and acetyltransferases in a given enterobacterial strain might confer resistance to both gentamicin and amikacin, although such combinations, with MICs of Ͼ30 g/ml, are rare. Second, this test is not compatible with nonfermenters, such as Pseudomonas aeruginosa and Acinetobacter baumannii, which may also produce 16S rRNA methylases (8,9).…”
Section: Resultsmentioning
confidence: 98%
“…These suggest that the higher gentamicin resistance of A. baumannii isolates A1 and A8 when compared to A9 may be related to the higher expression levels of O05286 and D0CCK1, while the higher Q2FCY1 expression level may contribute more to strong gentamicin resistance in A1. The generation of aminoglycoside-modifying enzymes has been reported in multidrug-resistant A. baumannii isolates [Shi et al, 2005;Zhou et al, 2010]. Moreover, another two aminoglycoside-modifying enzymes, 3-N-aminoglycoside acetyltransferase and 16S rRNA methylase, were found to have significantly lower levels in A. baumannii isolate A9 compared to A8, which may be the reason why A. baumannii A9 was susceptive while isolate A8 was intermediately resistant to gentamicin.…”
Section: Discussionmentioning
confidence: 95%